Avalanche hazard in plain area of Sakhalin Island - D. A. Bobrova (Лëд и снег, 2015)
Avalanche danger for the lowland areas at the Sakhalin Island is discussed in the paper, and the slopes of 5 m height are considered as avalanching. We need to evaluate the potential danger to the man, and denote these territories as avalanche dangerous. On the plains of Sakhalin Island avalanche catchments have a height up to 25 m, and the slope of 20 to 60 degrees. River terraces in height up to 50 m are found in the lower parts of mountain rivers where the width of the valley is more than 100 m.